2017
DOI: 10.3164/jcbn.16-108
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exercise training on nitric oxide, blood pressure and antioxidant enzymes

Abstract: The relationship between exercise training and nitric oxide-related parameters was examined in a cross-sectional study and an intervention study. A cross-sectional study using 184 employees was conducted to observe the association of exercise habits with serum arginase (ELISA and activity), l-arginine, l-citrulline, l-ornithine, NOx, exhaled nitric oxide, blood pressure, FEV1%, hs-CRP, HDL-cholesterol, IgE, and life style factors. An intervention study was also conducted to evaluate the changes of serum argina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
51
1
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(59 citation statements)
references
References 50 publications
2
51
1
5
Order By: Relevance
“…(35) nitric oxide (NO) involved in vascular endothelial function increases after aerobic exercise training. (36) MBP is determined by cardiac output and peripheral vascular resistance (e.g., peripheral endothelial function). We found that ankle MBP increased from baseline after the 75-g OGTT after the intervention in the CON group, whereas ankle MBP did not change after the intervention in the PAI group.…”
Section: Discussionmentioning
confidence: 99%
“…(35) nitric oxide (NO) involved in vascular endothelial function increases after aerobic exercise training. (36) MBP is determined by cardiac output and peripheral vascular resistance (e.g., peripheral endothelial function). We found that ankle MBP increased from baseline after the 75-g OGTT after the intervention in the CON group, whereas ankle MBP did not change after the intervention in the PAI group.…”
Section: Discussionmentioning
confidence: 99%
“…Further research is needed in order to clarify these mechanisms. The increase in circulating Klotho following exercise training may be the result of an increase in the transcription factor peroxisome proliferator‐activated receptor γ, a decline in angiotensin II type I receptor signalling and reduction of oxidative stress, endothelin 1, TGFβ and inflammation that follow exercise training (Faul et al., 2011; Kawamura et al., 2004; Saetre et al., 2011; Tsukiyama, Ito, Nagaoka, Eguchi, & Ogino, 2017; Wilund, 2007) and lead to an increase in the expression of Klotho mRNA and protein (Lim et al., 2012; Mitobe et al., 2005; Saito, Ishizaka, Mitani, Ohno, & Nagai, 2003; Zhang et al., 2008). Also, the increase in shear stress, hypoxia, endothelial biomarker changes, stimulation of peroxisome proliferator‐activated receptor γ coactivator 1α, and increase in antioxidant capacity may be the stimulus to increase Klotho following HIIT, but clarification of these mechanisms is needed and more research is needed to understand the mechanisms that are effective in exercise training‐induced changes in plasma and myocardial levels of Klotho.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, blocking NO actually reduced exercise performance in both of these groups below that observed in the untrained WT group, supporting the major role of the NO pathway in mediating the enhanced exercise performance found in both these groups. Although NO is known to be a mediator of exercise performance [17, 21], and is involved in exercise training [28, 30], this is the first demonstration that the increased exercise performance induced by exercise training can not only be completely eliminated by NO blockade, but can be reduced below levels observed in untrained animals. One reason for this novelty is that NO blockade did not reduce exercise performance in untrained WT mice, the model that has been examined most extensively in prior studies.…”
Section: Discussionmentioning
confidence: 99%